(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the pattern of paediatric bony tumours or tumour like lesions presenting to the Department of Orthopaedics & Spine Surgery Ghurki Trust Teaching Hospital Lahore in the past five years. Methods:This retrospective Cohort study was conducted in Department of Orthopaedics & Spine Surgery Ghurki Trust Teaching Hospital Lahore.The records of all children with bony lesions fulfilling the inclusion criteria who presented to our hospital in time period extended from 1st April 2015 to 1st April 2021 were reviewed.The type of lesion, gender, site, histological type and treatment of each bony lesion was documented. Results: The total number of children with tumour or tumour like bony lesions were 212.The mean age was 11.55±3.12 years. Male children were 145(68.39%) and female were 67(31.60%). The most common tumor site was distal femur noted in 65 (30.66%) children. Osteosarcoma was the predominant bone tumour diagnosed in 118(55.6%) children followed by with Ewing sarcoma in 32(15.1%), chondrosarcoma in 20(9.43%) and osteoid osteoma in 12(5.6%) chilfren. Excisional biopsy was the most common(38.20%,n=81) surgical intervention followed by incisional biopsy in 52(24.52%) children. Conclusion: Tumour or tumour like bony lesions were more frequently detected in male children than in female children.Distal femur was the most commonly involved bone.Osteosarcoma was the most commonly diagnosed primary malignant bone tumour while Osteochondroma and Aneurysmal Bone Cysts were the most frequently detected benign bony lesions.